Aplicabilidade do programa Lean Seis Sigma na redução do Lead Time de licitações de obras e serviços de engenharia - Rosemary Geralda Barbosa Gomes (2013)
The research approaches the applicability of the Lean Six Sigma programme in the Lead Time reduction to engineering constructions and services bidding. A survey was conducted regarding the introduction and evolution of management techniques applied in the Brazilian public sector. The work was developed from the analysis of legal gaps and the diversity in the interpretation of bidding procedures in the engineering field. The work brought resolution to to one of the matters connected to a specific legal gap: bidding modality adjustment for hiring an engineering service through a case study. The study proved the perfect viability of employing the quality program at hand aiming to eliminate what doesnt add value to the process and also considering the constitutional principle of efficiency which leans upon the better possible use of public resources in order to avoid waste.